A mixed silica-fume airport pavement concrete and a preparation method thereof

CN122916544APending Publication Date: 2026-10-16AVIC KAIDIAN AIRPORT ENG CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611227740.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-13
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0005]本申请提供了一种混掺硅灰机场道面混凝土及其制备方法,解决了现有传统机场道面混凝土脆性大、抗折与抗疲劳性能低、易引发裂缝与剥落病害从而导致服役寿命短的技术问题

Benefits of technology

[0016] This application provides a method for preparing airport pavement concrete mixed with silica fume. By defining the gradation of ordinary Portland cement, sand, and graded aggregate, and specifying the proportions of silica fume and water-reducing agent, the high surface activity and dispersibility of the microparticles in silica fume are utilized to fill the micropores between hydrated cement particles. The silica in the silica fume reacts with the calcium hydroxide generated during hydration in a secondary pozzolanic reaction to form a high-strength CSH gel, refining the pore structure. Based on a water-reducing agent-based segmented ultrasonic pre-anchoring process, a dual synergy of chemical steric hindrance and physical energy cavitation is achieved, eliminating secondary agglomeration defects of microsilica, improving the flexural and compressive strength of airport pavement concrete at all ages, reducing permeability, and extending the service life of airport pavement under complex heavy-load environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916544A_ABST
    Figure CN122916544A_ABST
Patent Text Reader

Abstract

The application discloses a kind of mixed silica ash airport pavement concrete and preparation method thereof.The method comprises: obtaining raw materials, including cement 30.0-35.4%, sand 15.2-22.1%, stone 35.0-47.7%, water, water reducing agent and silica ash with cement weight 3.0-8.0%;Dry mixing output aggregate dry mixture;Silica ash is mixed with part of water to prepare silica ash suspension;Water reducing agent is dissolved in the remaining water to prepare water reducing agent solution;Solution and suspension are sequentially added to dry mixture, and mixed and stirred to output concrete.The application can reduce the early shrinkage rate and chloride ion permeation electric quantity of concrete, improve the compressive and flexural strength, enhance the pavement erosion resistance and prolong the service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of building materials and chemical formulations, specifically relating to a silica fume-blended airport pavement concrete and its preparation method. Background Technology

[0002] Airport pavements, as the infrastructure for aircraft takeoff, landing, taxiing, and parking, bear a demanding engineering mission. Throughout their service life, airport pavements not only need to withstand the high-frequency dynamic impacts and alternating fatigue loads from heavy aircraft, but also inevitably endure prolonged exposure to sunlight and rain, freeze-thaw cycles caused by significant temperature differences, and the corrosive environment of complex chemical media such as de-icing salts in winter. These conditions require pavement concrete to possess high compressive strength, flexural strength, and excellent durability.

[0003] Currently, traditional airport pavements primarily use conventional silicate cement concrete. Traditional pavement concrete is a brittle material system, with numerous capillary pores left by moisture evaporation and micro-cracks caused by incomplete hydration within its internal structure. These microscopic defects result in low macroscopic tensile strength, flexural strength, and fatigue resistance. Under the combined effects of repeated aircraft loads and environmental erosion, traditional airport pavements are prone to structural cracks, surface spalling, slab breakage, and pumping. This increases subsequent maintenance and repair costs and the risk of flight delays.

[0004] In my country, the actual service life of most cement concrete airport pavements often falls short of the design standard of thirty years, with the average service life hovering around fifteen to twenty years. Some high-traffic airports even experience structural damage to their load-bearing pavements within just a few years of construction. The technical shortcomings of traditional pavement concrete—high brittleness and insufficient resistance to spalling and erosion—are becoming increasingly apparent. There is an urgent need to develop a new type of high-performance pavement concrete material and corresponding preparation process that can refine the pore structure, improve density, and enhance overall mechanical and durability properties. Summary of the Invention

[0005] This application provides a silica fume-blended airport pavement concrete and its preparation method, which solves the technical problems of existing traditional airport pavement concrete being brittle, having low flexural and fatigue resistance, and being prone to cracking and spalling, thus resulting in short service life.

[0006] To achieve the above objectives, the first aspect of this application provides a method for preparing airport pavement concrete mixed with silica fume, comprising: obtaining raw materials, wherein the raw materials comprise, by weight percentage, 30.0% to 35.4% ordinary Portland cement, 15.2% to 22.1% sand, and 35.0% to 47.7% aggregate; wherein the raw materials further comprise water, silica fume, and a water-reducing agent; based on the weight of the ordinary Portland cement, configuring a water-cement ratio of 0.36 to 0.40, controlling the silica fume content to be 3.0% to 8.0%, and configuring the effective solids content of the water-reducing agent to be 0.16% to 0.22%; the aggregate comprises large stones with a particle size range of 18 mm to 25 mm, medium stones with a particle size range of 10 mm to 18 mm, and small stones with a particle size range of 5 mm to 10 mm, controlling the mass ratio of the large stones, the medium stones, and the small stones to be 7:8:4. The ordinary Portland cement, the sand, and the aggregate are dry-mixed to output a dry aggregate mixture. Extract a first predetermined portion of water, accounting for 30% to 50% of the total mixing water. Mix the silica fume with the first predetermined portion of water and perform forced stirring for 5 to 10 minutes to output a silica fume suspension. Obtain the remaining second predetermined portion of water and dissolve the water-reducing agent in the second predetermined portion of water to output a water-reducing agent solution. Add the water-reducing agent solution and the silica fume suspension sequentially to the dry aggregate mixture and perform forced stirring to output the resulting silica fume-blended airport pavement concrete.

[0007] Further, the total amount of water-reducing agent is divided into a first portion of water-reducing agent accounting for 25% to 30% of the total weight and a remaining second portion of water-reducing agent. The step of extracting a first predetermined portion of water accounting for 30% to 50% of the total mixing water, mixing the silica fume with the first predetermined portion of water, and performing forced stirring for 5 to 10 minutes to output a silica fume suspension is specifically configured as follows: the volume of the first predetermined portion of water is limited to 40% of the total mixing water; the first portion of water-reducing agent is mixed and dissolved with the first predetermined portion of water; then, the full amount of silica fume is added for mixing treatment, outputting a silica fume suspension with surface anchoring solids. The step of obtaining the remaining second predetermined portion of water, dissolving the water-reducing agent in the second predetermined portion of water, and outputting a water-reducing agent solution is specifically configured as follows: the second portion of water-reducing agent is dissolved in the remaining second predetermined portion of water, outputting the water-reducing agent solution.

[0008] Further, the step of mixing and dissolving the first portion of water-reducing agent with the first preset portion of water, and then adding the full amount of silica fume for mixing treatment to output the silica fume suspension with surface anchoring solids is specifically configured as follows: An ultrasonic reactor equipped with a cold water circulation jacket is provided. An aqueous solution containing the first portion of water-reducing agent is pumped into the ultrasonic reactor, and all the silica fume is added at a uniform rate while maintaining stirring. An ultrasonic generator configured in the ultrasonic reactor is activated to perform ultrasonic cavitation treatment on the mixture in the ultrasonic reactor, controlling the ultrasonic cavitation energy density within the range of 600 joules per milliliter to 850 joules per milliliter. During the ultrasonic cavitation treatment, the cold water circulation jacket is simultaneously activated to control the temperature of the mixture in the ultrasonic reactor within a preset safe temperature range. A synergistic dispersion operation is performed using physical cavitation and the chemical steric hindrance effect of the first portion of water-reducing agent to output the silica fume suspension with surface anchoring solids.

[0009] Further, the step of dry-mixing the ordinary silicate cement, the sand, and the gravel to output the aggregate dry mix is ​​specifically configured as follows: Large stones, medium stones, and small stones are sequentially added to a forced twin-shaft mixer to perform a first-stage initial mixing, controlling the initial mixing time to last 20 to 30 seconds, outputting synthetic coarse aggregate. The ordinary silicate cement and the sand are then added to the forced twin-shaft mixer to perform a second-stage dry mixing, controlling the dry mixing time to last 40 to 60 seconds, outputting the aggregate dry mix.

[0010] Further, the step of sequentially adding the water-reducing agent solution and the silica fume suspension to the dry aggregate mixture, and performing forced stirring to output the prepared silica fume-blended airport pavement concrete is specifically configured as follows: while continuously stirring, the water-reducing agent solution is uniformly sprayed into the dry aggregate mixture through a spray pipe, and stirring is maintained for 30 to 45 seconds to form a water-reducing agent solution film coating the surface of the aggregate. Subsequently, the silica fume suspension is injected into the mixing system, and a second forced stirring is performed for 90 to 120 seconds to output the prepared silica fume-blended airport pavement concrete.

[0011] Furthermore, the sand is hard river sand, the fineness modulus of the sand is configured to be 2.4 to 2.8, and the mud content of the sand is controlled to be less than 1.2%.

[0012] Furthermore, the ordinary silicate cement has a strength grade greater than or equal to 42.5, and the tricalcium aluminate content in the ordinary silicate cement is less than or equal to 8.0% by mass.

[0013] Furthermore, the mass percentage content of SiO2 in the silica fume is greater than 85%, and the specific surface area of ​​the silica fume is greater than 60,000 square centimeters per gram.

[0014] The second aspect of this application provides a silica fume-blended airport pavement concrete, wherein the raw materials of the silica fume-blended airport pavement concrete include, by weight percentage, 30.0% to 35.4% ordinary Portland cement, 15.2% to 22.1% sand, and 35.0% to 47.7% aggregate; wherein the raw materials further include water, silica fume, and a water-reducing agent; based on the weight of the ordinary Portland cement, the water-cement ratio is configured to be 0.36 to 0.40, the amount of silica fume is 3.0% to 8.0%, and the effective solid content of the water-reducing agent is 0.16% to 0.22%; the aggregate comprises large stones with a particle size range of 18 mm to 25 mm, medium stones with a particle size range of 10 mm to 18 mm, and small stones with a particle size range of 5 mm to 10 mm, and the mass ratio of the large stones, the medium stones, and the small stones is configured to be 7:8:4.

[0015] Furthermore, the silica fume-blended airport pavement concrete is configured with macroscopic mechanical characteristics and microscopic durability characteristics; the macroscopic mechanical characteristics include: a compressive strength greater than or equal to 50 MPa and a flexural strength greater than or equal to 7.0 MPa after 28 days of standard curing; the microscopic durability characteristics include: a chloride ion permeation charge less than or equal to 685 coulombs after 56 days of standard curing.

[0016] This application provides a method for preparing airport pavement concrete mixed with silica fume. By defining the gradation of ordinary Portland cement, sand, and graded aggregate, and specifying the proportions of silica fume and water-reducing agent, the high surface activity and dispersibility of the microparticles in silica fume are utilized to fill the micropores between hydrated cement particles. The silica in the silica fume reacts with the calcium hydroxide generated during hydration in a secondary pozzolanic reaction to form a high-strength CSH gel, refining the pore structure. Based on a water-reducing agent-based segmented ultrasonic pre-anchoring process, a dual synergy of chemical steric hindrance and physical energy cavitation is achieved, eliminating secondary agglomeration defects of microsilica, improving the flexural and compressive strength of airport pavement concrete at all ages, reducing permeability, and extending the service life of airport pavement under complex heavy-load environments. Attached Figure Description

[0017] Figure 1 This is a flowchart of the preparation method of airport pavement concrete mixed with silica fume provided in the embodiments of this application.

[0018] Figure 2 This is a logical structure block diagram of the pre-anchored ultrasonic dispersion system provided in the embodiments of this application.

[0019] Explanation of reference numerals in the attached figures

[0020] 201-Ultrasonic reaction vessel; 202-Cold water circulation jacket; 203-Ultrasonic generator; 204-Mechanical agitator; 205-Suspension pump pipeline. Detailed Implementation

[0021] To make the objectives, technical solutions, and advantages of this application clearer, the following detailed description is provided in conjunction with the accompanying drawings and specific embodiments. It should be emphasized that the specific embodiments described below are merely illustrative of this application and are not intended to limit the scope of this application. All other technical embodiments obtained by those skilled in the art based on the descriptions in this application are within the scope of protection of this application.

[0022] like Figure 1 As shown in one embodiment of this application, a main foundation scheme for the preparation method of silica fume-blended airport pavement concrete is provided. This foundation preparation method relies on conventional forced mixing machinery and mainly includes the following sequential process steps:

[0023] Step S101: Obtain raw materials, which include, by total weight percentage, 30.0% to 35.4% ordinary silicate cement, 15.2% to 22.1% sand, 35.0% to 47.7% gravel, water, silica fume, and water-reducing agent.

[0024] The proportions and physicochemical parameters of all raw materials are strictly limited to meet the requirements of high-load-bearing, dry-hard concrete for airport pavements. The water-cement ratio of the formulation is 0.36 to 0.40. The weight of silica fume is controlled to be 3.0% to 8.0% of the weight of ordinary Portland cement. The effective solids content of the water-reducing agent is 0.16% to 0.22% of the weight of ordinary Portland cement. In a more specific implementation, ordinary Portland cement with a strength grade of 42.5 or higher is selected, and the mass percentage content of tricalcium aluminate in the ordinary Portland cement is controlled to be less than or equal to 8.0%. Low tricalcium aluminate content can reduce the early hydration heat peak of cement and suppress early temperature shrinkage cracks caused by excessive temperature gradients. The water used complies with the requirements of the "Standard for Water Used in Concrete" JGJ63-06.

[0025] For fine aggregate, the sand is preferably hard river sand used in construction, with a particle size distribution in the second gradation zone and a fineness modulus between 2.4 and 2.8. The mud content of the sand is controlled to be less than 1.2% to prevent mud powder from coating the aggregate surface and weakening the bonding force in the interfacial transition zone. For coarse aggregate, the gravel is synthetically graded artificial limestone crushed stone. To improve the interlocking and interlocking effect of the skeleton and reduce the porosity of the concrete, the gravel is limited to three continuous particle size ranges: large stones (18 mm to 25 mm), medium stones (10 mm to 18 mm), and small stones (5 mm to 10 mm). The mass ratio of the large stones, medium stones, and small stones is controlled to be 7:8:4.

[0026] For mineral admixtures, high-purity fine silica fume is selected, requiring a specific surface area greater than 60,000 square centimeters per gram. The active silica content in the silica fume must be greater than 85% by mass. The water-reducing agent is preferably a polycarboxylate-based high-efficiency water-reducing agent with a water reduction rate of not less than 25%. It should be noted that the water content of the polycarboxylate-based high-efficiency water-reducing agent itself, as a solvent, must be deducted in equal amounts during mix design to maintain a constant actual water-cement ratio. The mix design output of this application is for dry-hard concrete with a slump controlled at less than 20 mm. It should be noted that the specific material parameters mentioned above are only preferred configuration examples. Those skilled in the art can use similar qualified equivalent materials based on local building material supply conditions, but should strive to ensure that the above-mentioned constraints are met.

[0027] Step S102: Dry mix the ordinary silicate cement, the sand and the gravel to output the dry aggregate mixture.

[0028] The weighed large, medium, and small stones are sequentially added to a forced twin-shaft mixer for the first stage of initial mixing, which lasts for 20 to 30 seconds. This action utilizes the mechanical friction and tumbling of the coarse aggregate to allow the three different particle sizes of crushed stone to interweave in physical space, resulting in a composite coarse aggregate. The ordinary silicate cement and sand are then added to the forced twin-shaft mixer in one step for the second stage of dry mixing, which lasts for 40 to 60 seconds, resulting in a dry aggregate mixture. This two-stage, step-by-step dry mixing process avoids the phenomenon of cement powder agglomerating before the coarse aggregate is mixed.

[0029] Step S103: Extract a first preset portion of water, accounting for 30% to 50% of the total mixing water volume, mix the silica fume with the first preset portion of water, and perform forced stirring for 5 to 10 minutes to output a silica fume suspension.

[0030] Directly adding silica fume can cause tiny silica particles to easily aggregate into spheres, making them difficult to disperse in dry, hard concrete with a low water-cement ratio. In this step, a portion of the mixing water is extracted separately, and silica fume with a high specific surface area is immersed in the water. The strong shear force provided by the high-speed mixing equipment is used to break up the large particle agglomerates, thus pre-preparing a silica fume suspension with a certain degree of physical stability.

[0031] Step S104: Obtain the remaining second preset portion of water, dissolve the water-reducing agent in the second preset portion of water, and output the water-reducing agent solution.

[0032] Step S105: The water-reducing agent solution and the silica fume suspension are added sequentially to the dry aggregate mixture, and a forced stirring operation is performed to output the silica fume-blended airport pavement concrete.

[0033] While maintaining continuous high-speed mixing by the mixer blades, the water-reducing agent solution prepared in step S104 is uniformly sprayed into the dry aggregate mixture through a spray pipe located above the mixing tank, and mixing is maintained for 30 to 45 seconds. Physically, this allows the water-reducing agent solution to preferentially coat the surface of the sand and gravel aggregates and cement particles, forming an adsorbed water film and prematurely activating the steric hindrance effect of the water-reducing agent. The silica fume suspension prepared in step S103 is then injected into the mixing system, and a second forced mixing is performed for 90 to 120 seconds. This allows the fine silica fume particles carrying active silica to wedge into the gaps between the cement particles dispersed by the water-reducing agent, completing homogenization and outputting the prepared silica fume-blended airport pavement concrete. It can then be poured into molds, allowed to stand, sealed with a film, demolded after 24 hours, and cured at room temperature before testing. Through a step-by-step alternating wet and dry preparation process, the homogeneity of the silica fume-blended system at low slump is improved, and early macroscopic mechanical strength is activated.

[0034] Based on the above embodiments, and addressing the inherent defect in traditional processes where silica fume, despite pre-dispersion, is still prone to significant secondary micro-agglomeration in pure water systems due to Brownian motion and van der Waals forces, another embodiment of this application provides an extended solution with stronger dispersion efficiency: "water-reducing agent segmentation pre-anchoring ultrasonic process." Figure 2 As shown, this advanced process relies on a pre-anchored ultrasonic dispersion system. The system includes a batching unit with fluid control valves and a core ultrasonic reaction vessel 201. The ultrasonic reaction vessel 201 is externally encased in a cold water circulation jacket 202, has a mechanical agitator 204 mounted at its internal axis, and is equipped with an array of ultrasonic generators 203 on its sidewalls or bottom. The output end of these generators is connected to a suspension pump pipeline 205 for quantitatively discharging the slurry.

[0035] This embodiment restructures the mixing sequence of the water-reducing agent and water. After obtaining the full amount of the formulation raw materials, the total amount of the water-reducing agent is forcibly divided into a first portion of water-reducing agent accounting for 25% to 30% of the total weight and the remaining second portion of water-reducing agent. The volume of the aforementioned extracted first preset portion of water is limited to 40% of the total water volume.

[0036] In this process, the steps for preparing the silica fume suspension include: pumping a first predetermined portion of water, accounting for 40% of the total mixing water volume, into the ultrasonic reaction vessel 201; adding the first portion of water-reducing agent; and turning on the mechanical stirrer 204 for 2 minutes to allow it to mix and dissolve. After confirming that the first portion of water-reducing agent has dissolved into a homogeneous solution, the full amount of silica fume is uniformly added into the ultrasonic reaction vessel 201. The ultrasonic generator 203 is then activated to perform high-frequency ultrasonic cavitation treatment on the liquid-solid mixture in the ultrasonic reaction vessel 201.

[0037] At the ultrasonic processing control level, to prevent insufficient ultrasonic energy from causing disintegration failure or energy overload from triggering slurry degradation, the input sound field energy is constrained, controlling the ultrasonic cavitation energy density within the range of 600 joules per milliliter to 850 joules per milliliter. In a preferred embodiment, the control logic can be constructed using the following formula to calculate and feedback-adjust the ultrasonic cavitation energy density:

[0038]

[0039] Among them, E v The formula represents the ultrasonic cavitation energy density, expressed in joules per milliliter; P represents the actual power output of the ultrasonic generator 203 during operation, expressed in watts; t represents the duration of ultrasonic cavitation treatment, expressed in seconds; and V represents the total volume of silica fume suspension injected into the ultrasonic reaction vessel 201 and treated, expressed in milliliters. This energy density formula is used to construct control logic, quantitatively assessing the actual mechanical stripping energy input to a unit volume within the dispersion system, thereby establishing a mapping relationship between the cavitation microjets intensity and the silica fume agglomerate fracture threshold. In a specific implementation, the ultrasonic generator 203 is configured with a frequency of 28 kHz, a constant output power P of 800 W, a treated suspension volume V of approximately 4200 mL, and a single continuous ultrasonic treatment time t of 3600 seconds. The ultrasonic cavitation energy density E is calculated by substituting into the formula. v It is approximately 685.7 J / mL, falling within the target range of 600-850 J / mL.

[0040] During the ultrasonic cavitation treatment, the cold water circulation jacket 202 is simultaneously activated. The temperature of the mixture in the ultrasonic reaction tank 201 is controlled within a preset safe temperature range using external circulating refrigerant. A synergistic dispersion operation is performed using physical cavitation and the chemical steric hindrance effect of the first portion of the water-reducing agent. The surface-anchored silica fume suspension is then output to the outside through the suspension pump pipeline 205. The second portion of the water-reducing agent is dissolved in the remaining second preset portion of water, and the water-reducing agent solution for main stirring is output. This solution is then sequentially mixed with the aggregate in the main forced mixer.

[0041] By introducing this extended process, a dual synergy of physical and chemical processes was achieved. When the ultrasonic cavitation bubbles collapsed and exploded within the gaps of the silica fume agglomerates, the microjets tore apart the agglomerate surface. Due to the pre-dissolution of the first portion of the water-reducing agent, polycarboxylic acid molecules, utilizing their free carboxyl groups, preemptively adsorbed onto the freshly exfoliated active sites of silica. The long side chains of the polycarboxylic acid molecules extended outwards on the surface of the individual, fine silica fume particles, forming a steric barrier layer. This blocked the secondary recombination induced by van der Waals forces at the moment the ultrasound stopped, ensuring that the tiny silica fume particles could participate in the subsequent main hydration reaction of the airport pavement concrete in monomer form.

[0042] To demonstrate the performance improvement brought about by the pre-anchoring ultrasonic process of the water-reducing agent, this application provides a set of extended comparative test data. All tests in this set maintained a silica fume content of 7%.

[0043] Example 6-A: Using this method, 28% of the total amount of water-reducing agent was extracted and added to water accounting for 40% of the total mixing water. The ultrasonic cavitation energy density was 685.7 J / mL, and the cold water was controlled at 22℃.

[0044] Comparative Example 6-B: A basic high-speed stirring process was used, and silica fume was mixed only with pure water. No water-reducing agent was introduced in advance, and there was no ultrasonic cavitation.

[0045] After curing, tests were conducted in accordance with national standards such as the "Standard for Test Methods of Long-Term Performance and Durability of Ordinary Concrete". The test results are shown in Table 6-1.

[0046] Table 6-1 Comparison of performance test results between Example 6-A and Comparative Example 6-B

[0047]

[0048] As shown in Table 6-1, compared to the baseline process of physical dispersal using pure water, Example 6-A prepared using this extended scheme exhibited an increased 28-day compressive strength from 62.39 MPa to 71.15 MPa and a flexural strength from 6.95 MPa to 7.82 MPa. Because the silica fume was dispersed, filling capillary pores and cutting off interconnecting pathways, the core durability indicator—56-day chloride ion permeation charge—decreased from 1240 coulombs to 685 coulombs. The early 14-day shrinkage rate decreased from 415 to 320, indicating that localized stress concentration and self-shrinking microcracks caused by silica fume agglomerates were suppressed. These data demonstrate that the pre-anchoring process activated the physical filling and pozzolanic activity of the silica fume, enhancing the service life of airport pavements under complex corrosive environments.

[0049] In another embodiment of this application, a silica fume-blended airport pavement concrete product prepared by the above-described preparation method is provided. To verify the macroscopic reliability of the mix proportioning system, mixing ratios with different silica fume content gradients were systematically designed. The absolute mass and corresponding total weight percentage of cement, sand, and aggregate in the specific raw material mix proportions, as well as the detailed proportions of water and silica fume based on cement, are shown in Table 1. All large, medium, and small aggregates used are limestone crushed stone; the free water in all polycarboxylate superplasticizers has been converted into the water usage specified in the table.

[0050] Table 1. Mixing ratios of the embodiments

[0051]

[0052] The mixtures numbered 1 to 9 in Table 1 were prepared and standard cylindrical and prismatic specimens were cast. After natural curing for 7, 14, and 28 days, rigorous flexural and compressive strength tests were conducted using a hydraulic servo machine. The test results are summarized in Table 2.

[0053] Table 2 Performance Test Results

[0054]

[0055] Based on the data evolution patterns in Tables 1 and 2, the physical and chemical basis for the superior properties of the airport pavement concrete is explained. For dry-hardened airport concrete, flexural strength is a key indicator. In the early stage, at low dosages, compared to test group 1 without silica fume, the 7-day flexural strength of test group 2 jumped from 4.53 MPa to 5.43 MPa, demonstrating the catalytic effect of silica fume on early flexural development. In the middle stage, as the silica fume dosage increased to 6%-7%, flexural performance significantly improved, with the 14-day flexural strength of test group 6 reaching 7.21 MPa. During the 28-day standard setting period, the flexural strength at all dosages steadily exceeded industry norms.

[0056] Considering the necessary compressive strength, within the 7-day early curing window, test group 6 achieved a compressive strength of 51.35 MPa, representing a 51.43% increase compared to the baseline group without silica fume. During the 28-day evaluation period, appropriate amounts of silica fume enabled the compressive strength to exceed the 50 MPa technical threshold. Test number 6 achieved a 28-day compressive strength of 62.39 MPa, meeting the instantaneous ground impact response requirements of large and medium-sized wide-body passenger aircraft.

[0057] The physical essence behind the synergistic improvement in both macroscopic mechanical and microscopic durability characteristics lies in the fact that the ultrafine silica fume particles selected in this application fill the capillary network that should remain after cement hydration, constructing a dense framework through a physical compaction effect. A secondary chemical reaction occurs: during cement hydration, relatively loosely structured, water-soluble calcium hydroxide crystals are released; however, the large amount of amorphous active silica contained in the pre-dispersed micro-silica in this application can capture and react with the calcium hydroxide crystals during the curing process, transforming them into a large amount of dense, chemically stable CSH gel. This replacement of microscopic material morphology eliminates the weak links in the interfacial transition zone, prevents the seepage path of corrosive chloride ions, and endows the airport pavement concrete with high flexural and compressive toughness, as well as excellent resistance to freeze-thaw cycles.

[0058] The above description is merely a few preferred embodiments of this application and is not intended to limit this application. Any modifications, equivalent substitutions, alterations, and improvements made within the principles and spirit of this application should be included within the protection scope of this application.

Claims

1. A method for preparing airport pavement concrete mixed with silica fume, characterized in that, include: The raw materials are obtained, comprising, by weight percentage, 30.0% to 35.4% ordinary Portland cement, 15.2% to 22.1% sand, and 35.0% to 47.7% gravel; wherein, the water-cement ratio is configured to be 0.36 to 0.40, the weight of silica fume is controlled to be 3.0% to 8.0% of the weight of the ordinary Portland cement, and the effective solids content of the water-reducing agent is configured to be 0.16% to 0.22% of the weight of the ordinary Portland cement; the raw materials also include water, silica fume, and water-reducing agent; based on the weight of the ordinary Portland cement, the water-cement ratio is configured to be 0.36 to 0.40, the silica fume content is controlled to be 3.0% to 8.0%, and the effective solids content of the water-reducing agent is configured to be... The effective solids content is 0.16% to 0.22%; the aggregates include large stones with a particle size range of 18 mm to 25 mm, medium stones with a particle size range of 10 mm to 18 mm, and small stones with a particle size range of 5 mm to 10 mm, and the mass ratio of the large stones, medium stones, and small stones is controlled to be 7:8:4; the ordinary silicate cement, the sand, and the aggregates are dry-mixed to output a dry aggregate mixture; a first preset portion of water, accounting for 30% to 50% of the total mixing water, is extracted, the silica fume is mixed with the first preset portion of water, and forced stirring is performed for 5 to 10 minutes to output a silica fume suspension; the remaining second preset portion of water is obtained, the water-reducing agent is dissolved in the second preset portion of water, and a water-reducing agent solution is output; The water-reducing agent solution and the silica fume suspension are added sequentially to the dry aggregate mixture, and a forced stirring operation is performed to output the silica fume-blended airport pavement concrete.

2. The method for preparing airport pavement concrete mixed with silica fume as described in claim 1, characterized in that, The total amount of water-reducing agent is divided into a first portion of water-reducing agent accounting for 25% to 30% of the total weight and a remaining second portion of water-reducing agent. The step of extracting a first preset portion of water accounting for 30% to 50% of the total mixing water, mixing the silica fume with the first preset portion of water, and performing forced stirring for 5 to 10 minutes to output a silica fume suspension is specifically configured as follows: the volume of the first preset portion of water is limited to 40% of the total mixing water; the first portion of water-reducing agent is mixed and dissolved with the first preset portion of water; then, the full amount of silica fume is added for mixing treatment, outputting a silica fume suspension with surface anchoring solids. The step of obtaining the remaining second preset portion of water, dissolving the water-reducing agent in the second preset portion of water, and outputting a water-reducing agent solution is specifically configured as follows: the second portion of water-reducing agent is dissolved in the remaining second preset portion of water, outputting the water-reducing agent solution.

3. The method for preparing airport pavement concrete mixed with silica fume as described in claim 2, characterized in that, The step of mixing and dissolving the first portion of water-reducing agent with the first preset portion of water, and then adding the full amount of silica fume for mixing treatment to output the silica fume suspension with surface anchoring solids is specifically configured as follows: providing an ultrasonic reactor equipped with a cold water circulation jacket; pumping the aqueous solution containing the first portion of water-reducing agent into the ultrasonic reactor, and uniformly adding all the silica fume while maintaining stirring motion; activating the ultrasonic generator configured in the ultrasonic reactor to perform ultrasonic cavitation treatment on the mixture in the ultrasonic reactor, controlling the ultrasonic cavitation energy density within the range of 600 joules per milliliter to 850 joules per milliliter; during the ultrasonic cavitation treatment, simultaneously activating the cold water circulation jacket to control the temperature of the mixture in the ultrasonic reactor within a preset safe temperature range, and performing a synergistic dispersion operation using physical cavitation and the chemical steric hindrance effect of the first portion of water-reducing agent to output the silica fume suspension with surface anchoring solids.

4. The method for preparing airport pavement concrete mixed with silica fume as described in claim 1, characterized in that, The step of dry mixing the ordinary silicate cement, the sand, and the gravel to output the aggregate dry mix is ​​specifically configured as follows: the large stones, the medium stones, and the small stones are sequentially added to a forced twin-shaft mixer to perform the first stage of initial mixing, controlling the initial mixing time to last 20 to 30 seconds, and outputting the synthetic coarse aggregate; the ordinary silicate cement and the sand are added to the forced twin-shaft mixer to perform the second stage of dry mixing, controlling the dry mixing time to last 40 to 60 seconds, and outputting the aggregate dry mix.

5. The method for preparing airport pavement concrete mixed with silica fume as described in any one of claims 1 to 4, characterized in that, The step of sequentially adding the water-reducing agent solution and the silica fume suspension to the dry aggregate mixture and performing forced stirring to output the prepared silica fume-blended airport pavement concrete is specifically configured as follows: under continuous stirring, the water-reducing agent solution is uniformly sprayed into the dry aggregate mixture through a spray pipe, and stirring is maintained for 30 to 45 seconds to form a water-reducing agent solution film coating the surface of the aggregate; then the silica fume suspension is injected into the mixing system, and a second forced stirring is performed for 90 to 120 seconds to output the prepared silica fume-blended airport pavement concrete.

6. The method for preparing airport pavement concrete mixed with silica fume as described in claim 1, characterized in that, The sand is hard river sand with a fineness modulus of 2.4 to 2.8 and a mud content of less than 1.2%.

7. The method for preparing airport pavement concrete mixed with silica fume as described in claim 1, characterized in that, The ordinary silicate cement has a strength grade greater than or equal to 42.5, and the tricalcium aluminate content in the ordinary silicate cement is less than or equal to 8.0% by mass.

8. The method for preparing airport pavement concrete mixed with silica fume as described in claim 1, characterized in that, The silica fume contains more than 85% SiO2 by mass and has a specific surface area of ​​more than 60,000 square centimeters per gram.

9. A type of airport pavement concrete mixed with silica fume, characterized in that, The raw materials of the silica fume-blended airport pavement concrete include, by weight percentage, 30.0% to 35.4% ordinary Portland cement, 15.2% to 22.1% sand, and 35.0% to 47.7% aggregate; wherein, the raw materials also include water, silica fume, and a water-reducing agent; based on the weight of the ordinary Portland cement, the water-cement ratio is configured to be 0.36 to 0.40, the amount of silica fume is 3.0% to 8.0% of the weight of the ordinary Portland cement, and the effective solids content of the water-reducing agent is 0.16% to 0.22% of the weight of the ordinary Portland cement; the aggregate includes large stones with a particle size range of 18 mm to 25 mm, medium stones with a particle size range of 10 mm to 18 mm, and small stones with a particle size range of 5 mm to 10 mm, and the mass ratio of the large stones, the medium stones, and the small stones is configured to be 7:8:

4.

10. The airport pavement concrete with silica fume as described in claim 9, characterized in that, The mixed silica fume airport pavement concrete has macroscopic mechanical characteristics and microscopic durability characteristics; the macroscopic mechanical characteristics include: a compressive strength greater than or equal to 50 MPa and a flexural strength greater than or equal to 7.0 MPa after 28 days of standard curing; the microscopic durability characteristics include: a chloride ion permeation charge less than or equal to 685 coulombs after 56 days of standard curing.